E-Commerce Dispute Resolution Through Online Dispute Resolution - Jusman Dg. Takenang; Ma'ruf Akib; Sudirman Sudirman; Wahyudi Umar; Fe Fikran Alfurqon (SASI, 2025)
Introduction: The rapid growth of the e-commerce industry has brought significant economic benefits. Still, it also raises challenges regarding dispute resolution that is efficient, fair and meets the needs of all parties.